ANALYSIS OF TOURISM SECTOR ON COMMUNITY INCOME IN GORONTALO PROVINCE IN 2015-2019 - Husain, Ferawaty; Dai, Sri Indriyani S; Santoso, Ivan (Jurnal REP (Riset Ekonomi Pembangunan), 2022)
This study aims to determine (1) the effect of the number of tourists on people's income in the province of Gorontalo, (2) the effect of the number of hotel accommodations on the income of the people in the province of Gorontalo, (3) the average length of stay on the income of the people in the province of Gorontalo. This study uses quantitative methods using panel data, and the data collection technique in this study is documentation. Researchers collect archival data at the Central Statistics Agency of Gorontalo Province. Data analysis in this research used multiple linear regression analysis. The results of this study indicate (1) there is a positive and significant relationship between the number of tourist visits and the income per capita of the community (PCI). If the number of foreign and local tourists visiting Gorontalo Province increases, the people's per capita income will increase. (2) The number of hotels has a positive and significant effect on the income per capita of the community, meaning that if the number of hotels increases, the income per capita of the community will increase. (3) The average length of stay has a negative and significant effect on people's per capita income. An interese in the average length of stay can reduce a community’s per capita income.